Optimizations of Placenta Extracellular Matrix‐Loaded Silk Fibroin/Alginate 3D‐Printed Scaffolds Structurally and Functionally for Bone Tissue Engineering - Zahra Bashiri; Zahra Khosrowpour; Ali Moghaddaszadeh; Davod Jafari; Sanaz Alizadeh; Hajar Nasiri; Houman Parsaei; Zahra Keshtkaran; Meghdad Abdollahpour‐Alitappeh; Farshad Bargrizaneh; Behzad Rezaei; Sara Simorgh; et al. (Engineering in Life Sciences)
ABSTRACT Recent interest has been focused on extracellular matrix (ECM)–based scaffolds totreat critical‐sized bone injuries. In this study, urea was used to decellularize and solubilize human placenta tissue. Then, different concentrations of ECM were composited with 8% alginate (Alg) and 12% silk fibroin (SF) for printing in order to produce a natural 3D construct that resembled bone tissue. The physical and biological features of the printed structures were evaluated entirely in vitro. Finally, a rat model was employed to examine the optimal 3D printed scaffold (5% ECM) as a bone transplant for the healing of cranial bone lesions. The present investigation demonstrated that decellularizing placental tissue fragments led to efficient removal of cell debris. In addition, a remarkable improvement in the printed scaffolds' mechanical and biological properties was observed by increasing the ECM concentration. The histology studies and real‐time PCR results demonstrated the acceleration of bone regeneration in the bone lesions treated with 5%ECM‐SF/Alg at 4 and 8 weeks after implantation. Overall, these results proved that the placental ECM‐printed scaffolds could potentially construct biomimetic grafts to reconstruct significant bone defects and now promise to proceed with clinical studies.